(untitled) (Research, Society and Development, 2021)
The thermal energy generation system based on the burning of LPG was implemented to provide thermal energy to replace a boiler based on burning vegetable oil, in order to perform the drying of agrochemical products such as granules dispersible in water (WDG) , by means of two vibro-fluidized beds. A mathematical modeling was developed, whose objective is to predict process temperatures, mainly the temperature of the air mixture at the entrance of the Dryers. Calculations of LPG consumption for different products and process conditions are also an important result of this work, as it is possible to foresee consumption and costs. The modeling can predict the system conditions for new products, allowing their advance study. MS Excel was used as software. Literature equations were used for comparative calculations with the supplier’s original design data. The adiabatic flame temperatures were calculated, obtaining a margin of error of 1.79%, the hot air temperatures in pipelines and the temperatures of the air mixture for the Dryers, which were compared with real data of operation, whose Calculation results showed a margin of error of 2.56% and 2.87% for the first and second dryers, respectively, demonstrating that the modeling is applicable. The results showed that the LPG-based system is better in terms of thermal performance and is an automated and instrumented system, which provides excellent process control.